2017
DOI: 10.1007/s10549-017-4554-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an aerobic exercise bout 24 h prior to each doxorubicin treatment for breast cancer on markers of cardiotoxicity and treatment symptoms: a RCT

Abstract: An exercise bout performed 24 h prior to every doxorubicin treatment did not have an effect on markers of subclinical cardiotoxicity, but had a positive systemic effect on hemodynamics, musculoskeletal symptoms, mood, and body weight in women with breast cancer. A single exercise bout prior to chemotherapy treatments may be a simple clinical modality to reduce symptoms and weight gain among women with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 46 publications
3
107
0
1
Order By: Relevance
“…Based on preclinical evidence [23, 24], we previously investigated the effect of 30 min of vigorous-intensity treadmill walking performed 24 h prior to every anthracycline treatment (i.e., one session per 2–3 week cycle) on markers of cardiotoxicity and treatment symptoms in women with breast cancer [25, 26]. This is a highly feasible approach as patients are usually scheduled to attend the treatment center for blood tests and physician examination the day prior to treatments and this day would also correspond with the nadir of symptoms from the previous treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on preclinical evidence [23, 24], we previously investigated the effect of 30 min of vigorous-intensity treadmill walking performed 24 h prior to every anthracycline treatment (i.e., one session per 2–3 week cycle) on markers of cardiotoxicity and treatment symptoms in women with breast cancer [25, 26]. This is a highly feasible approach as patients are usually scheduled to attend the treatment center for blood tests and physician examination the day prior to treatments and this day would also correspond with the nadir of symptoms from the previous treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the exercise session significantly attenuated NT-proBNP at 24–48 h after the first treatment, which is a circulating biomarker of anthracycline-related cardiac damage and cardiac events. At treatment completion, performing the session prior to each therapy had prevented an increase in resting heart rate (highly prognostic of mortality) and cardiac output, and reduced body weight and prevalence of sore muscles, low back pain and depressed mood relative to usual care [25, 26]. …”
Section: Introductionmentioning
confidence: 99%
“…In relation to DOX cardiotoxicity, an exercise bout performed 24 h prior to doxorubicin treatment reduced circulating NT-proBNP and increased systolic function in female breast cancer patients indicative of reduced acute DOX cardiotoxicity [151]. However, in the same patient group, exercise did not have an effect on markers of subclinical cardiotoxicity 7-14 days after DOX, even though there was a positive systemic effect on haemodynamics, musculoskeletal symptoms, mood and body weight [152]. The intensity and timing of exercise with respect to DOX treatment may alter what cardioprotective effect can be achieved and it may be beneficial to assess different exercise protocols in cancer patients on DOX chemotherapy.…”
Section: Exercisementioning
confidence: 95%
“…Another study showed that eight weeks of endurance exercise prior to chronic induction of ADR could reduce cardiac toxicity by reducing serum LDH levels (26). Kirkham et al suggested that shortterm endurance exercise before treatment of cancer patients with ADR could reduce serum cTnT levels (27). In general, previous reports indicated that endurance exercise could protect the cardiomyocytes against the ADR-induced cardiac toxicity.…”
Section: Discussionmentioning
confidence: 99%